BENEFITS OF RADIAL SHOCK WAVE THERAPY AND LASER THERAPY ON MYALGIA LOW BACK PAIN: BENEFITS OF RADIAL SHOCK WAVE THERAPY AND LASER THERAPY ON MYALGIA LOW BACK PAIN - Jehaman, Isidorus; Ginting, Raynald Ignasius; Berampu, Sabirin; Tantangan, Redi (JURNAL PENGMAS KESTRA (JPK), 2022)
Low Back Pain (LBP) does not cause death, but causes individuals to become unproductive so that it will cause an enormous economic burden for individuals, families, communities and the government. Indonesian BPS data explains that people over 15 years of age have health problems. With increasing age, the anatomical structure and function of tissues will decrease, such as muscles, bones and joints, ligaments and other soft tissues. These changes are relevant to a person's decrease in activity. Pain is a major problem in patients with LBP disorders. Physiotherapy measures to overcome these complaints are extracorporeal shock wave therapy and laser. Physiotherapeutic intervention using shock wave therapy and extracorporeal laser methods can be given to LBP myalgia patients through community service activities carried out at Grandmed Lubuk Pakam Hospital. To evaluate the results of the intervention, the measuring tool used is the Verbal Analog Scale (VAS). This activity was attended by 12 respondents who complained of low back pain. Before and after the intervention the value will be measured using the VAS. Based on the results of the last evaluation, it can be seen that the respondents' pain complaints before and after the intervention experienced withdrawal, namely 5.8 (moderate pain) before the intervention and after the intervention the value became 0.8 (mild pain). The results of these actions prove that physiotherapy interventions such as radial shock wave therapy and laser therapy are useful/effective in dealing with complaints of LBP myalgia.